HUBUNGAN IKLIM MIKRO DAN BAHAN ORGANIK TANAH DENGAN EMISI CO2 DARI PERMUKAAN TANAH DI HUTAN ALAM BABAHALEKA TAMAN NASIONAL LORE LINDU, SULAWESI TENGAHEFFECT OF MICROCLIMATE AND SOIL ORGANIC MATTER ON SOIL ORGANIC MATTER ON SOIL... - Ade Irawan; Tania June (PERHIMPI (Indonesian Association of Agricultural Meteorology), 2011)
Soil respiration and rate of CO2 emission is determined by its temperature and its organic matter. Canopy opening of a pristine forest affect the amount of radiation energy that are able to go down the canopy and determine the microclimate variability at the forest floor and rate of CO2 emission. This resesarch was conducted at Babahaleka Forest Lore Lindu National Park, Central Sulawesi and supported under the cooperation of IPB-STORMA (Stability of Rainforest Margin) project, with an objective to determine the effect of soil temperature as a consequence of different level of canopy opening (and incoming radiation) on CO2 emission from soil respiration process. Soil CO2 emission was measured through CO2 gas sampling using a closed chamber method and analyzed using CO2 gas analyzer. Measurement of soil temperature, air temperature, relative humidity and soil organic matter were conducted at each CO2 gas sampling sites for further analysis of correlation between them. It was shown that soil temperature and soil surface temperature, soil moisture and air temperature affected soil respiration and CO2 emission from the soil surface. Average soil surface CO2 fluxes was 299.15 mgCO2m-2h-1, with fluxes from more open canopy cover was higher than that from a closed canopy cover, 329.33-375.77 mgCO2m-2h-1 and 209.24-304.18 mgCO2m-2h-1 respectively.